LITERASI AGAMA SEBAGAI ALTERNATIF PENDIDIKAN MORAL - Cucu Nurzakiyah (Jurnal Penelitian Agama, 2018)
Abtract: Global development requires not only intelligent human beings but also moral human beings. Moral humans don't just show up. Schools become one of the educational institutions that play an important role in instilling moral values. These moral values can be instilled and strengthened by critical reading of various texts or discourse, which is called literacy. Literacy, including religious literacy, needs to be taught to students to make them able to live in the midst of this modern society. In learning moral values, learners do not just know and do without knowing the purpose of the value carried out, but they have to understand why such values are important. Religious literacy, in addition to fostering interest in reading, also trains students to be able to criticize the sources of knowledge related to religion or the values he gets both in the form of text (book), oral, visual, and digital. Through deep understanding of the sources of knowledge, we can choose various existing value alternatives and apply them as a manifestation of self-actualization. Keywords: literacy, religion, education, and Morals.